Penerapan Metode Pembelajaran Drill Berbantuan Media Cerita Bergambar untuk Meningkatkan Keterampilan Membaca Nyaring pada Siswa Sekolah Dasar - Maidini Tamara; Iis Aprinawati; Fadhilaturrahmi Fadhilaturrahmi (MODELING: Jurnal Program Studi PGMI, 2023)
Study this aim for enhancement Skills read loud student class II SDN 014 Kuok year the 2022/2023 academic year, totaling 13 students . Method study this is Study Action Class (PTK) carried out in two cycle learning . Every cycle consist from two meeting and four Step learning namely : planning , implementation , observation and reflection . Time study held on month August 2022. Technique data collection in the form of documentation , observation and test . Results Skills read loud student class II SDN 014 Kuok on pre-action average value 52 ,30 with percentage 38% completeness . On cycle I meeting I average value 52.69 with percentage completeness study 38% and on Cycle I meeting II experienced enhancement with the average value is 56.15 with percentage completeness study 46%. On cycle II meeting I experienced enhancement also with the mean value is 61.53 with percentage completeness study 62% and on cycle II meeting II experienced enhancement again with the average value is 64.61 with percentage completeness learn 85%. With thereby could concluded that with application method learning drill story media help pictorial could increase Skills read loud student class II SDN 014 Kuok.